1970
DOI: 10.1097/00132586-197002000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid Treatment and Surgery. 2. The Management of Steroid Cover

Abstract: In the preceding paper 1 criteria have been suggested for deciding which patients treated with steroid drugs required cover for surgery. The investigation presented here was designed to determine what form this cover should take.Patients already receiving synthetic steroids were given operative cover according to one of three different regimes, in an attempt to simulate the plasma cortisol (hydrocortisone) levels seen during and after surgery in normal subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

1978
1978
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…The drug groups are composed of steroidal and non-steroidal anti-inflammatory agents, and can later include several agents, such as antimalarials, sulfasalazine, penicillin, azathioprine, methotrexate, and cyclosporine A. The anesthesiologist should be attentive to the adverse effects of these drugs, which can influence anesthetic technique 17 .…”
Section: Therapymentioning
confidence: 99%
“…The drug groups are composed of steroidal and non-steroidal anti-inflammatory agents, and can later include several agents, such as antimalarials, sulfasalazine, penicillin, azathioprine, methotrexate, and cyclosporine A. The anesthesiologist should be attentive to the adverse effects of these drugs, which can influence anesthetic technique 17 .…”
Section: Therapymentioning
confidence: 99%
“…This is followed by 100 mg intramuscularly every 6 hours for 48e72 hours. Intravenous hydrocortisone produces inadequately sustained steroid levels 11 and so 25 mg at induction should be followed by an infusion at 5 mg/hour. 12 Risks of glaucoma, cataracts, hypersensitivity reactions and candidiasis have been reported, but are infrequent.…”
Section: Immunomodulatorsmentioning
confidence: 99%
“…Differences in the methods of assessment of the HPA axis probably account for the huge variability in reported recovery times. Plumpton and Besser suggested 2 months as the maximum interval following treatment during which recovery of the HPA may be incomplete [6], while La Rochelle and colleagues found that the duration of therapy, total steroid dose and highest steroid dose administered did not affect HPA recovery [38]. Based on this evidence, we suggest that patients who have taken steroids in excess of 10 mg prednisolone, or equivalent, within 3 months of surgery, should be considered to have some degree of HPA suppression and receive a low-dose replacement regimen according to the magnitude of surgery.…”
Section: Steroid Treatment Regimensmentioning
confidence: 99%
“…Of the 20 patients currently receiving long-term steroid therapy, 10 patients were receiving replacement therapy for Addison's disease, hypopituitarism or following adrenalectomy and the remaining 10 patients were receiving immunosuppressive therapy for unspecified conditions [6]. The patients treated previously had received prednisolone, or equivalent, in doses ranging from 5 to 50 mg.day ¹1 for between 6 days and 10 years; the interval since treatment varied from 3 days to 24 months.…”
mentioning
confidence: 99%